A[-]human Time. A Quasi-Architectural Tale in Three Acts - Pala, Giacomo (Scenari, 2021)
This paper is divided in three main parts – a-human future; a-human present and a-human- past. These sections – with a fourth (Imagining a[-]Human Time) – are meant as thoughts on our relationship with technology. The paper starts with the anthropocentric definition of modernity, in architecture, developing the following hypothesis: technology might become an ahuman affair, independent from us. Consequently, architecture may become a self-regulated object while we will be extinct. The second section – a[-]human present – develops further the investigation by showing that we have always been in a recursive evolutionary process in which technologies and languages influence each-other, to the point that the human may be defined as the outcome of the ahuman. The third part – a[-]human past – investigates how technology redefines our past by means of post-production and remixing of information. Finally, it is discussed how one of the few practices we can focus on in order to maintain a certain cultural relevance – as architects, at least – is to focus on aesthetics in order to re-present viable alternatives to the present-state of things.